A histopathologic study of urinary bladder tumors at tertiary care center in Mid-Western region of Nepal - Goyal, Binita; Rao, Sheshagiri; Sahi, Rajina; Jaiswal, Subechhya (Asian Journal of Medical Sciences, 2018)
Background: Urinary bladder cancer is an important cause of morbidity and mortality due to urological conditions. It is tenth most common cancer overall in both sexes. It is seventh most common cancer overall and second most common cancer of genitourinary tract in males. Ninety five percent of bladder tumors are epithelial and the rest are mesenchymal, of which majority are primary urothelial tumors. Urothelial tumors are classified into infiltrating urothelial carcinoma with its variants and non-invasive urothelial neoplasias. Tumor stage is the strongest prognostic parameter. Aims and Objectives: The current study was designed with an aim to elucidate the histologic pattern of bladder tumors and observe whether any association between histologic grade and muscle invasion exists. Materials and Methods: This descriptive study was carried out on 84 cases of urinary bladder tumors received in Department of Pathology, College of Medical Sciences and Teaching Hospital during a time period of 5 years from January 2012 to December 2016. Results: The mean ± SD of age of presentation was 63±13 years with a male female ratio 3.2:1. Ninety-five percent cases were primary epithelial tumors and 93% cases were of urothelial origin. Low grade papillary urothelial carcinoma was the most common urothelial tumor (40.5%) followed by high grade papillary urothelial carcinoma (34.5%). Some rare types like primary adenocarcinoma and small cell carcinoma were also seen in this study (1.2% each). Muscle invasion was significantly higher in high grade (66%) as compared to low grade papillary urothelial carcinoma (3%). Muscle tissue was absent in 8 (9.5%) cases. Conclusion: There is relationship of histologic grade with aggressiveness of tumor. Most of the high grade tumors are muscle invasive at presentation. Submission of muscle tissue is important for optimal patient management. Asian Journal of Medical Sciences Vol.9(6) 2018 45-50